Biocontrol Activity, Mode of Action, and Colonization of Aureobasidium pullulans Dmg 30 DEP on Controlling Early Blight Disease on Tomato Plant - Wawan Setiawan; Suryo Wiyono; Toga Pangihotan Napitupulu; Atit Kanti; Idris Idris; Masrukhin Masrukhin; Efi Toding Tondok; I Nyoman Sumerta; I Made Sudiana (HAYATI Journal of Biosciences, 2022)
We investigated the biocontrol activity of A. pullulans Dmg 30 DEP against Alternaria solani causal agent of early blight. Biocontrol activity was tested by the in vivo and ad planta. Biocontrol activity were tested by investigating the antibiosis capabilities with dual culture method, paper dish assay, two-compartment petri dish assay, and trapping and identification of volatile organic compounds (VOCs) with GC-MS. Lysis activity was examined by observing the clear zone formed by growing yeast on chitin agar and skim milk agar. The ability of hyperparasitism was assessed by the agar block method, and observed by light microscopy and scanning electron microscopy (SEM). The results showed that A. pullulans Dmg 30 DEP plays a role in the suppression of early blight disease at 106 cells/ml and 107 cells/ml yeast cell density. The mechanism involved in biocontrol activity is the production of VOCs, the production of chitinase and protease enzymes, the production of siderophore and hyperparasitism. The result shows that A. pullulans Dmg 30 DEP was colonizing the tomato leaves following the areole.